Fatigue crack propagation behavior of polyether ether ketone under biaxial loading. Issue 6 (23rd April 2021) - Meng, Guolong; Hu, Jiaqi; Liu, Zhenduo; Gao, Hong; Gao, Lilan
Abstract: Polyether ether ketone (PEEK) has become a promising material in total joint replacement. However, it still faces the risk of fatigue fracture during service. In this paper, the effects of biaxial stress ratio λ, cyclic stress ratio R, and load phase difference θ on fatigue crack propagation (FCG) behavior of PEEK are investigated. In the case of vertical cracks, results show that the FCG rate of PEEK increases with the R value, while decreases with the increase of λ value. Furthermore, the effective stress intensity factor range Δ K eff can uniformly describe the biaxial FCG behavior at different cyclic stress ratios. In the case of 45° slant cracks, compared with mode‐I intensity factor range Δ K I, the energy release rate range Δ G is more accurate for describing the FCG behavior under various load phase differences. In addition, the investigation on the 45° crack propagation path shows that a bifurcated Y‐shaped crack appears under 180° load phase difference, while no bifurcated crack appears under 90° load phase difference and uniaxial loading. Three different methods are used to predict the crack propagation path. The comparison results show that the maximum circumferential stress (MTS) criterion can well predict the crack propagation path under out‐of‐phase biaxial loading and uniaxial loading. Abstract :